Prevalence of Hepatitis C in Hemodialysis Patients in Indonesia - Anto Wahyudin; Ariadi Humardhani; Syafruddin A. R. Lelosutan (Fakultas Kedokteran Universitas Jenderal Soedirman, 2026)
Hepatitis C (HCV) is a blood-borne viral infection and a major cause of global morbidity and mortality. Indonesia is one of six countries contributing to 50% of the global HCV burden, with a prevalence of 0.5% in the general population. HCV infection is more frequently observed in patients with chronic kidney disease undergoing hemodialysis due to nosocomial transmission. This study employed a literature review method by searching articles published between 2015 and 2025 in Google Scholar, PubMed, and ProQuest, yielding 11 eligible studies. The analysis shows that the prevalence of HCV among hemodialysis patients in Indonesia ranges from 3.7% to 56.3%, with the highest rate reported at H. Adam Malik General Hospital Medan (56.3%) and the lowest at Banyu Bening Hospital Boyolali (3.7%). Most infected patients are male and over 45 years of age. These variations indicate that male sex and older age serve as risk factors for HCV infection in hemodialysis patients.